The Fibonacci sequence is defined using the recurrence formula:
fn+2 = fn+1 + fn for n ≧ 1 with f1 = 1 and f2 = 1.
The sequence begins 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, 233, ...
Theorem: Every fourth number in the Fibonacci sequence is divisible by 3.
i.e. The subsequence f4n is divisible by 3 for n ≧ 1.
Proof: When n = 1, f4 = 3 which is divisible by 3.
Assume that the statement is true for n = k, so f4k is divisible by 3. Now,
3f4k+1 is divisible by 3 and so too is 2f4k using the inductive hypothesis. Hence f4(k+1) is divisible by 3 which means that the statement is true when n = k+1. So f4n is divisible by 3 for n ≧ 1 by mathematical induction.
Now assume that the statement is true for n = i for all 1 ≤ i ≤ k for some k∈ℕ and k ≥ 2. In standard mathematical induction you have a single induction hypothesis; if you have multiple inductive hypotheses you can use “strong induction” to prove the result for n=k+1. So from our inductive hypotheses we can say that:
When n=k+1, we have
So the statement is true for n=k+1 and hence true for n ≥ 1 by strong induction.
Theorem: Binet's formula for the nth term of the Fibonacci sequence
Proof: First note that φ²=φ+1, since
So two base cases are satisfied. Now assume that the statement is true for n = i for all 1 ≤ i ≤ k for some k∈ℕ and k ≥ 2. When n=k+1, we have
So the statement is true for n=k+1 and hence true for n ≥ 1 by strong induction.
Theorem: Each term of the Fibonacci sequence can be expressed as a sum of binomial coefficients
Here the nCr terms are summed as long as n ≥ r.
Proof: This will require Pascal's combinatorial identity,
To see this,
Now, when n=1 and n=2, we have
So two base cases are satisfied. Now assume that the statement is true for n = i for all 1 ≤ i ≤ k for some k∈ℕ and k ≥ 2. When n=k+1, we have
So the statement is true for n=k+1 and hence true for n ≥ 1 by strong induction.
Comments